Apexification of an Endodontically Failed Permanent Tooth with an Open Apex: A Case Report with Histologic Findings - Sundus Bukhary (Medicina)
The management of an endodontic failure in a traumatized tooth with an open apex presents a major dilemma. The arrest of root growth after traumatic injury is a substantial consequence of pulpal necrosis. Conventional endodontic treatment procedures will be challenging by the resulting thin, fragile dentinal walls, which will impede the appropriate debridement and optimal apical sealing. Apexification is a well-established procedure that is designed to treat or preserve a tooth with an incomplete root apex and necrotic pulpal tissue by promoting the formation of a calcified apical barrier through the application of a bioactive substance at the root apex. The present case report demonstrates a successful apexification procedure for an endodontically failed permanent central incisor with an open apex with a two-year follow-up time. The clinical and radiographical results revealed the absence of signs and symptoms and the formation of hard tissue at the root apex. The tooth was extracted for prosthodontic reasons and processed for histologic examination. The histologic evaluation revealed dentin-like and cementum-like tissues formed at the apical barrier.